If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -14 = -24 Reorder the terms: -14 + x = -24 Solving -14 + x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + x = -24 + 14 Combine like terms: -14 + 14 = 0 0 + x = -24 + 14 x = -24 + 14 Combine like terms: -24 + 14 = -10 x = -10 Simplifying x = -10
| 2x-1.5=6 | | 2x^2+6y^2+3=4x^2-8y+4 | | 6(x-2)=-3x+42 | | 2+4x=x+11 | | 5x-3(x-1)-7=2(x-2) | | 4t+9+(2t+7)= | | -6=6+k | | -3(x-4)+7=-2x | | (4x^2-3x)(6x+5)=0 | | 3x-25=11x-5+2x | | 5(x-3)=2x+21 | | 5y+2x=25 | | 26+4y-4=16y-13-5y | | 3x-0.25y=-2 | | x+0.20(3)=0.60(x+3) | | 22x+8-24x=7-9 | | 6-(5p+3)=6[(5p-3)-(p-7)] | | -4x+16=-11x+10 | | 10x+9-9x=15 | | x=-14-3x | | -10+18=m-9 | | -15=5(3q-10) | | -3x-5=5+2x | | -3t-4=7 | | -8x+10=-x+80 | | 7x=-47 | | 3(6+8R)-3(R+2)= | | 4k^2+26k-36=0 | | -5=x-9 | | 4(x+8)=-4(x-16) | | -0.01x^2+0.92x=0 | | 5e+10=25 |